Design, synthesis and molecular docking studies of some morpholine linked thiazolidinone hybrid molecules - War, Javeed Ahmad; Srivastava, Santosh Kumar; Srivastava, Savitri Devi (European Journal of Chemistry, 2016)
A novel series of morpoline linked thiazolidione hybrid molecules targeting bacterial enoyl acyl carrier protein (Enoyl-ACP) reductase were designed and synthesized through a three step reaction protocol, which involves simple reaction setup and moderate reaction conditions. The synthesized molecules were characterized with FT-IR, 1H NMR, 13C NMR and HRMS techniques. In vitro susceptibility tests against some Gram positive (Staphylococcus aureus and Bacillus subtilis) and Gram negative bacteria (Escherichia coli and Pseudomonas aeruginosa) gave highly promising results. Most of the molecules were found to be active against the tested bacterial strains. The most potent molecule (S2B7) gave MIC value of 2.0 µg/mL against Escherichia coli that was better than the reference drug streptomycin. Structure activity relationship showed nitro and chloro groups are crucial for bioactivity if present at meta position of arylidene ring in designed molecules. Molecular docking simulations against multiple targets showed that the designed molecules have strong binding affinity towards Enoyl-ACP reductase. Binding affinity of -8.6 kcal/mol was predicted for S2B7. Van der Waals forces, hydrogen bonding and hydrophobic interactions were predicted as the main forces of interaction.